Evaluation of Spot Urinary Calcium to Creatinine Ratio in Preeclampsia: A Cross Sectional Comparative Study - Begum, Hasina; Rahman, Md Nazibur; Ferdous, Menoka; Basak, Sankar Kumar; Yasmin, Nilufar; Parveen, Ayesha (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Preeclampsia (PE) is a pregnancy related condition leading to significant mortality and morbidity. A number of renal changes are seen in preeclampsia. Objectives: This study was designed to determine the association of calcium to creatinine ratio in a spot sample of urine with preeclampsia. Methodology: This cross-sectional comparative study was conducted in the Obstetrics & Gynaecology department of Dhaka Medical College, Dhaka, Bangladesh. Pregnant women with preeclampsia without complication and women with normal pregnancy without complications were selected for the study. Calcium, creatinine, Protein and calcium to creatinine ratio was measured in a spot urine sample of all these 150 subjects. Blood was also collected from all the cases for measurement of serum calcium, creatinine and uric acid. Results: A total of 150 pregnant women, 75 with preeclampsia without complication and 75 with normal pregnancy without complications were selected for the study. Significant difference between PE and normal group was observed in case of mean serum calcium and uric acid concentration but mean serum creatinine did not vary significantly. Urinary creatinine concentration did not show any significant difference. But mean urinary calcium concentration in spot sample of urine was significantly lower in preeclampsia than normal pregnant woman (3.45 ± 2.61 mg/dl vs 7.39 ± 2.80 mg/dl, p< 0.001). Similarly mean calcium to creatinine ratio in spot sample of urine was significantly lower in the pre-eclampsia than normal group (0.06 ± 0.05 vs 0.13 ± 0.06, p<0.001). Positive correlation was observed between urinary calcium/creatinine ratio and urinary calcium (r=+0.68, p<0.001) but negative correlation (r = - 0.39, p<0.001) noted between urinary calcium/creatinine and urinary protein. Conclusion: Spot urinary calcium and creatinine ratio decreases in preeclampsia. So spot urinary calcium and creatinine ratio can be regarded as a predictor for preeclampsia. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 14-20